Altered intra- and inter-regional functional connectivity of the visual cortex in individuals with peripheral vision loss due to retinitis pigmentosa. (June 2019) - Dan, Han-Dong; Zhou, Fu-Qing; Huang, Xin; Xing, Yi-Qiao; Shen, Yin
Highlights: RP individuals' synchronous neural activity changes decreased in V1. RP individuals showed intrinsic visual network disconnection. RP individuals had reorganized retino-thalamocortical pathways and dorsal streams. Visuospatial and stereoscopic vision were impaired in RP individuals. Abstract: This study investigated changes in intra- and inter-regional functional connectivity (FC) in individuals with retinitis pigmentosa (RP) by using regional homogeneity (ReHo) and FC methods. Sixteen RP individuals and 14 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging scans (fMRI). A combined ReHo and FC method was conducted to evaluate synchronization of brain activity. Compared with HCs, RP individuals had significantly lower ReHo values in the bilateral lingual gyrus/cerebellum posterior lobe (LGG/CPL). In FC analysis, the RP group showed decreased positive FC relative to the HC group, from bilateral LGG/CPL to bilateral LGG/cuneus (CUN) and to left postcentral gyrus (PosCG). In contrast, the RP group showed increased negative FC relative to the HC group, from bilateral LGG/CPL to bilateral thalamus, and decreased negative FC from bilateral LGG/CPL to right middle frontal gyrus (MFG), and to left inferior parietal lobule (IPL). Moreover, ReHo values of the bilateral LGG/CPL showed negative correlations with the duration of RP. FC values of the bilateral LGG/CPL-left IPL showed negative correlations with best-corrected visual acuity (BCVA) of the right eye and left eye in RP individuals. Our results reveal reduced synchronicity of neural activity changes in the primary visual area in RP individuals. Moreover, RP individuals showed intrinsic visual network disconnection and reorganization of the retino-thalamocortical pathway and dorsal visual stream, suggesting impaired visuospatial and stereoscopic vision.